Potato (Solanum tuberosum L.) variety development through hybridization: a new era in Bangladesh (Bangladesh Journal of Agricultural Research, 2014)
Systematic research on potato variety development has been in practice in Bangladesh since 1960, but until 2012, not a single variety was developed in this country through conventional breeding method, mainly due to the short day climatic factors which are not congenial for potato plants to flower. Due to the diversified efforts, TCRC scientists were able to make a breakthrough to overcome the climatic barriers. Flowering was induced in HYV potatoes and produce berries in the year 2000. After hybridization and continuous selection, five hybrid clones were placed in a RYT in 2010-11 from a batch of 502 kg F1 seedling tubers produced from 45 gram hybrid seeds of 2001-02. Based on the performances of SYT, AYT, RYT and on-farm trials, three varieties were released by the NSB in 2012 as BARI Alu-35, BARI Alu-36, and BARI Alu-37. Their genotype numbers are 4.5W, 4.26R, and 4.40, their mean yields were 38.36, 33.82, and 34.88 t/ha in AYT, 44.01, 41.84, and 40.58 t/ha in RYT, and 38.87, 38.52, and 37.53 t/ha in on-farm trials, respectively. DOI: http://dx.doi.org/10.3329/bjar.v38i4.19019 Bangladesh J. Agril. Res. 38(4): 637-646, December 2013